2017
DOI: 10.1002/gcc.22467
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of miR‐124‐3p and its target TP53INP1 in pediatric ependymoma

Abstract: Ependymoma is a malignant pediatric brain tumor, often incurable under the current treatment regimen. We aimed to evaluate the expression of microRNAs (miRs) in pediatric ependymoma tumors in an attempt to identify prognostic molecular markers which would lead to potential therapeutic targets. Following miR-array expression analysis, we focused on 9 miRs that correlated with relapse which were further validated by quantitative real-time PCR (qRT-PCR) in a cohort of 67 patients. Western blotting and immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
(83 reference statements)
1
14
1
Order By: Relevance
“…Fold change P-value Fold change P-value and miR-106b-5p differentiate between grade II and III ependymomas (12). Margolin-Miller et al demonstrated that high expression of miR-124-3p in ependymomas significantly correlated with the lower progression-free survival (28). Our observations of miR-203 expression in ependymomas are in contrast with previous findings (13) which shown that lower expression of miR-203 in ependymoma patients correlated to a trend to develop recurrences.…”
Section: G2 ---------------------------------------------------------contrasting
confidence: 79%
“…Fold change P-value Fold change P-value and miR-106b-5p differentiate between grade II and III ependymomas (12). Margolin-Miller et al demonstrated that high expression of miR-124-3p in ependymomas significantly correlated with the lower progression-free survival (28). Our observations of miR-203 expression in ependymomas are in contrast with previous findings (13) which shown that lower expression of miR-203 in ependymoma patients correlated to a trend to develop recurrences.…”
Section: G2 ---------------------------------------------------------contrasting
confidence: 79%
“…The 4 MicroRNA studies were all based on patients with gliomas (3 studies), or ependymomas (1 study); whereas the 2 Multiplexing and Immunoassays studies included cases of gliomas and meningiomas, respectively. Of note, only 1 study attempted to identify a biosignature on patients with gliomas by correlating a specific radiological pattern with the genetic profile of the tumor studied [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the three articles reported in Table 1 exploiting this methodology investigated a total of 22 different miRNA selected from a much larger pool of those initially considered by the authors at time of screening. Furthermore, the information obtained from studies on miRNA seem to be particularly useful at time of complementing them with those achievable with multiplexing or immunoassay proteomic studies [ 7 , 8 , 9 ]. This was the case also for the only study, among the selected ones, which resulted in successfully determining a biosignature of WHO Class II and III gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan and colleagues demonstrated miR-124-3p expression down-regulated amid bladder cancer tissues and cell lines, which played important role on malignant cellular multiplication, emigration and apoptosis [23]. Moreover, in the study of Margolin-Miller Y and colleagues, high miR-124-3p degree held strong connection to shortened progression-free survivals among ependymoma patients, which might represent a self-su cient indicator for prognoses in this disease [24]. Zhang and colleagues claimed miR-124-3p declined among breast cancer tissues and breast cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…They are unsatisfactory for screening of breast cancer. Recently, miR-124-3p was reported to be generally reduced in multiple tumors while its transfection suppresses the malignant cellular growth and migration [22][23][24][25]. For example, Gov E et al reported that miR-124-3p was a plausible indicator in ovarian cancer [22].…”
Section: Discussionmentioning
confidence: 99%